INTEGRASI BUSINESS WRITING DAN MARKETING SKILL SEBAGAI UPAYA MENINGKATKAN STRATEGI KOMUNIKASI DALAM PRAKTIK PEMASARAN MODERN - Muhammad Iqbal; Zuhrinal M. Nawawi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
In an increasingly competitive and digital business landscape, the ability to convey messages effectively has become a crucial aspect of marketing strategy. This study discusses the importance of integrating business writing and marketing skills as a means to enhance communication effectiveness in modern marketing practices. Clear, concise, and persuasive business writing strengthens brand messaging and builds corporate credibility. Meanwhile, marketing skills play a role in understanding the market, crafting targeted strategies, and tailoring messages to consumer needs. Using a literature review method, this research analyzes relevant sources to identify the relationship between these two skill sets and their impact on marketing communication effectiveness. The findings indicate that the synergy between effective business writing and adaptive marketing skills can enhance message appeal, strengthen customer relationships, and contribute to the overall success of marketing strategies.